Learning new relational categories by children with autism spectrum disorders, children with typical development and children with intellectual disabilities: effects of comparison and familiarity on systematicity. Issue 6 (12th February 2019) - Hetzroni, O. E.; Hessler, M.; Shalahevich, K.
Abstract: Background: Systematicity principle, used during analogical reasoning, enables building up deeper abstract concepts as part of structure mapping. The purpose of this study was to investigate structure mapping processes that occur during acquisition of new relational categories and to identify the learning patterns and systematicity of children with autism spectrum disorder (ASD) compared with intellectual and developmental disabilities (IDD) and typical development (TD). Comparison effect and level of familiarity were used to investigate structural mapping processes. Methods: Three groups of 24 children participated in the study. Using a computer program, participants were asked to select a perceptual or relational choice based on one or two standards using illustrations depicting new relational categories in various spatial configurations. Known, partially known and unknown illustrations were used in depicting three levels of familiarity. Results: All three groups selected perceptual choices when one standard was available (no comparison). However, when two standards were available, enabling a comparison, children with IDD and TD increased their tendency for selecting abstract relational categories, while children with ASD did not change their preference and continued selecting perceptual choices. Level of familiarity increased selection of relational choices among children with TD and IDD but not among children with ASD. Conclusions: Systematicity principle was evident mostly in the selection of relational choices by children with TD and IDD when the illustrations were known or partially known. Hence, even when an opportunity to compare and to use previously known information was available, structure mapping processes and systematicity were implemented to align information among children TD and IDD but failed to assist the learning of new relational categories among children with ASD.